PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN ALOKASI DANA DI DESA PINONOBATUAN BARAT KECAMATAN DUMOGA TIMUR KABUPATEN BOLAANG MONGONDOW - WILAR, CRECENSIA MERRY; Posumah, Johnny Hanny; Sondakh, Telly (Sam Ratulangi University, 2017)
ABSTRACT:The purpose of this study was to determine pemeberdayaan Community In Utilization VillageAllocation Fund (ADD) in the village of West Pinonobatuan the District East Dumoga Bolaang Mongondowas the Regulation of the Minister of Home Affairs Number 113 2014 About the Financial Management ofthe Village in Article 2 Paragraph 1 states that the financial management of the village should be based theprinciples of transparency, accountability and participatory. To determine the Community Empowermentin Rural Fund Allocation Utilization (ADD), the research method used was a qualitative descriptive studyconsists of 9 research informants. Empowering communities in the utilization of the Village FundAllocation (ADD) in the village of West Pinonobatuan has not been run in accordance with the principlesof financial pengelolaan villages of the principles of transparency, accountability and participatory. Basedon the results of field research on the utilization of public empowerment Village Fund Allocation (ADD)village government is not open to the public regarding the use of the Village Fund Allocation (ADD) so thatpeople do not know how much the cost disbursed to community empowerment; there is no accountability ineach realization of the program on the community; as well as the village government as the financialmanager of the Village Fund Allocation (ADD) partsispasi not involve the community in the form ofdecision-making, planning, implementation and the evaluation of results. In society to use the Village FundAllocation (ADD) in the hope the government village West Pinonobatuan District of East Dumoga as amanager and executor of every activity that comes from the Village Fund Allocation (ADD) should be basedon the principles of financial management of villages sebagimana contained in Regulation Home AffairsNumber 113 2014 About the Financial Management of the Village in Article 2 Paragraph 1 states that thefinancial management of the village should be based on the principles of transparency, accountability,danpartisipatif.Keywords: Development, Community, Utilization Village Fund Allocation.